ANALISIS LITERATUR TINGKAT KEBUGARAN JASMANI SISWA SEKOLAH MENENGAH PERTAMA - Nimrot Manalu; Maman Supriatman Mendrofa; Jhoseb Tarigan; Nurjani Jewakamat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of physical fitness among junior high school students based on findings from various scientific studies. The method used is a literature review by examining relevant national and international journal articles discussing students' physical fitness. The results indicate that the physical fitness level of junior high school students generally falls within the moderate category. Several factors influencing physical fitness include physical activity, nutritional status, gender, age, lifestyle, and participation in sports activities. Students who regularly engage in physical activities tend to have better physical fitness levels compared to those with sedentary lifestyles. Therefore, schools need to optimize physical education programs and extracurricular sports activities to improve students' physical fitness.